Small molecules targeting Pin1 as potent anticancer drugs - Zhang, Jing; Zhou, Wenwen; Chen, Yunyu; Wang, Yanchang; Guo, Zongru; Hu, Wenhui; Li, Yan; Han, Xiaomin; Si, Shuyi (Frontiers in Pharmacology, 2023)
Background: Pin1 is a member of the evolutionarily conserved peptidyl-prolyl isomerase (PPIase) family of proteins. Following phosphorylation, Pin1-catalyzed prolyl-isomerization induces conformational changes, which serve to regulate the function of many phosphorylated proteins that play important roles during oncogenesis. Thus, the inhibition of Pin1 provides a unique means of disrupting oncogenic pathways and therefore represents an appealing target for novel anticancer therapies. Methods: As Pin1 is conserved between yeast and humans, we employed budding yeast to establish a high-throughput screening method for the primary screening of Pin1 inhibitors. This effort culminated in the identification of the compounds HWH8-33 and HWH8-36. Multifaceted approaches were taken to determine the inhibition profiles of these compounds against Pin1 activity in vitro and in vivo, including an isomerization assay, surface plasmon resonance (SPR) technology, virtual docking, MTT proliferation assay, western blotting, cell cycle analysis, apoptosis analysis, immunofluorescence analysis, wound healing, migration assay, and nude mouse assay. Results:In vitro, HWH8-33 and HWH8-36 could bind to purified Pin1 and inhibited its enzyme activity; showed inhibitory effects on cancer cell proliferation; led to G2/M phase arrest, dysregulated downstream protein expression, and apoptosis; and suppressed cancer cell migration. In vivo, HWH8-33 suppressed tumor growth in the xenograft mice after oral administration for 4 weeks, with no noticeable toxicity. Together, these results show the anticancer activity of HWH8-33 and HWH8-36 against Pin1 for the first time. Conclusion: In summary, we identified two hit compounds HWH8-33 and HWH8-36, which after further structure optimization have the potential to be developed as antitumor drugs.